The use of the joint simultaneous integration methodology to measure the impact of certain macroeconomic variables on the GDP: ARDL model - Farouk Sahnoune; Salim Lagoune (Journal of Innovations and Sustainability)
Purpose. The objective of this study is to analyse the evolution of public expenditure, exports, imports, and gross domestic product (GDP) in Algeria over the past four decades (1980–2022). It aims to measure the impact of each of these macroeconomic variables (public expenditure, imports, and exports) on GDP during the study period, in the long and short term. Additionally, the study intends to identify the most significant economic variables influencing GDP in Algeria by constructing an econometric model (autoregressive model) based on economic theory and previous studies. These variables are considered the driving force and effective activator for improving GDP.